2021
DOI: 10.3390/molecules27010241
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry in Portugal—A Step towards Sustainable Chemical Synthesis

Abstract: In Portugal, publications with mechanochemical methods date back to 2009, with the report on mechanochemical strategies for the synthesis of metallopharmaceuticals. Since then, mechanochemical applications have grown in Portugal, spanning several fields, mainly crystal engineering and supramolecular chemistry, catalysis, and organic and inorganic chemistry. The area with the most increased development is the synthesis of multicomponent crystal forms, with several groups synthesizing solvates, salts, and cocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The simplest solution to the solvent use problem would be to develop methods that do not require solvents, such as mechanochemical methods [ 15 , 16 ]; however, this is not always feasible, and therefore, these compounds should be avoided or replaced by innocuous solvents for the same purposes [ 1 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest solution to the solvent use problem would be to develop methods that do not require solvents, such as mechanochemical methods [ 15 , 16 ]; however, this is not always feasible, and therefore, these compounds should be avoided or replaced by innocuous solvents for the same purposes [ 1 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that P–C bonds can be accessed from bis(trichlorosilyl)phosphide (Figure A, top), an intermediate directly prepared from phosphates, bypassing the hazardous P 4 . More recently, we demonstrated that phosphite can be produced from condensed phosphates and metal hydrides without traversing lower oxidation states than +3. , This “hydride phosphorylation” breakthrough was made possible by mechanochemistry, an increasingly popular technique that is often recognized as green and sustainable. Moreover, polyphosphates recovered from microorganisms were also shown to be promising substrates …”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemistry makes use of the absorption of mechanical energy (by molecules, ions, etc.) to promote chemical reactions [1]. Depending on the type of ball milling (mixer, planetary, or rolling mill), several sources of mechanical energy (impact, tension, and friction) can take place [2].…”
Section: Introductionmentioning
confidence: 99%